The mechanism of MMP14-positive tumor-associated fibroblast subsets in inhibiting PD-1 immunotherapy for esophageal cancer through exosomal tsRNA-10522 - Juzheng Wang; Chunlong Zheng; Jiayu Lu; Xinyao Xu; Guangyu Xiang; Jiahe Li; Jipeng Zhang; Xiaorong Mu; Qiang Lu (Functional & Integrative Genomics, 2024)

Magnolol-driven microbiota modulation elicits changes in tryptophan metabolism resulting in reduced skatole formation in pigs - Yuanfei Li; Yanchen Liu; Chunlong Mu; Changyi Zhang; Miao Yu; Zhimei Tian; Dun Deng; Xianyong Ma (Journal of Hazardous Materials, 2024)

Synthetic lethality in personalized cancer therapy - Ying Pang; Meng Cheng; Mu Chen; Kaijun Zhao; Yuanyuan Yin; Min Liu; Jing Zhang; Chunlong Zhong (Genome Instability & Disease, 2022)

Dietary fibres modulate the composition and activity of butyrate-producing bacteria in the large intestine of suckling piglets - Chunlong Mu; Lingli Zhang; Xiangyu He; Hauke Smidt; Weiyun Zhu (Antonie van Leeuwenhoek, 2017)

Age, introduction of solid feed and weaning are more important determinants of gut bacterial succession in piglets than breed and nursing mother as revealed by a reciprocal cross‐fostering model - Gaorui Bian; Shouqing Ma; Zhigang Zhu; Yong Su; Erwin G. Zoetendal; Roderick Mackie; Junhua Liu; Chunlong Mu; Ruihua Huang; Hauke Smidt; Weiyun Zhu (Environmental Microbiology, 2016)
Summary A reciprocal cross‐fostering model with an obese typical Chinese piglet breed and a lean Western breed was used to identify genetic and maternal effects on the acquisition and development gut bacteria from birth until after weaning. Pyrosequencing of 16S rRNA genes results revealed an age‐ and diet‐dependent bacterial succession process in piglets. During the first 3 days after birth, the bacterial community was relatively simple and dominated by Firmicutes with 79% and 65% relative abundance for Meishan and Yorkshire piglets, respectively. During the suckling period until day 14, the piglet breed and the nursing mother lead to increasing differentiation of the fecal bacterial community, with specific bacteria taxa associated with breed, and others with the nursing sow most likely due to its milk composition. Although the effect of nursing mother and the breed were evident through the suckling period, the introduction of solid feed and subsequent weaning were the major events occurring that dominated succession of the gut microbiota in the early life of piglets. This piglet cross‐fostering model is a useful tool for studying the effects of diet, host genetics and the environment on the development and acquisition of the gut microbiota and over longer studies the subsequent impact on growth, health and performance of pigs.

Genetic variation and phylogenetic analysis of porcine circovirus type 2 infections in central China - Chunlong Mu; Qingyuan Yang; Yina Zhang; Yonghui Zhou; Jixi Zhang; Darren P. Martin; Pingan Xia; Baoan Cui (Virus Genes, 2012)